Anti-N-Methyl-d-Aspartate Receptor Encephalitis that Developed after Herpes Encephalitis: A Case Report and Literature Review - Bektaş, Ömer; Tanyel, Tutku; Kocabaş, Bilge Aldemir; Fitöz, Suat; İnce, Erdal; Deda, Gülhis (Neuropediatrics, 2014)
Herpes encephalitis (HE) is among the most common forms of viral encephalitis. Earlier publications indicate the development of acyclovir-refractory choreoathetosis in patients with HE. These reports suggest the development of secondary autoimmunity in the pathogenesis of HE. Combined methylprednisolone and acyclovir treatment reduced the appearance of brain abnormalities relative to treatment with acyclovir alone in a mouse model of encephalitis. We describe a case of a 19-month-old previously healthy girl presenting with sudden onset seizures and loss of consciousness. Initial polymerase chain reaction (PCR) tests for the presence of herpes simplex virus (HSV) were negative as were the tests for the limbic encephalitis antibodies. Steroids were administered with acyclovir to treat suspected autoimmune encephalitis as a result of the patient history of varicella vaccination. HSV PCR testing was positive on the 5th day; however, steroid treatment was continued due to the positive response seen in the patient. Steroid therapy was reduced on the 25th day of treatment due to the development of upper respiratory tract infection and the patient developed orofacial dyskinesia and choreoathetoid movements on the 28th day. Antibodies against N-methyl-d-aspartate receptor were detected in the in the serum and cerebrospinal fluid (CSF) on the 28th day. This case is an example of the emergence of autoimmune symptoms in the pathogenesis of HE.
Keywords: herpes encephalitis; autoimmune encephalitis; pediatric; choreoathetoid movements; relapse; dyskinesia